2016
DOI: 10.1021/acs.jpca.6b08653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Free Radicals in Clathrate Hydrates of Furan, 2,3-Dihydrofuran, and 2,5-Dihydrofuran by Muon Spin Spectroscopy

Abstract: In addition to their importance as abundant hydrocarbon deposits in nature, clathrate hydrates are being studied as potential media for hydrogen and carbon dioxide storage, and as "nano-reactors" for small molecules. However, little is known about the behaviour of reactive species in such materials. We have employed muon spin spectroscopy to characterize various organic free radicals which reside as isolated guests in structure II clathrates. The radicals are formed by reaction of atomic muonium (Mu) with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…[41][42][43][44] In previous work we showed that two distinct radicals are formed when muonium reacts with furan. 36 Similar behaviour might well be expected for Mu addition to thiophene and pyrrole (Scheme 1) and this is indeed indicated by the TF-µSR spectra ( Fig. 1).…”
Section: Identification Of Radical Productssupporting
confidence: 81%
See 3 more Smart Citations
“…[41][42][43][44] In previous work we showed that two distinct radicals are formed when muonium reacts with furan. 36 Similar behaviour might well be expected for Mu addition to thiophene and pyrrole (Scheme 1) and this is indeed indicated by the TF-µSR spectra ( Fig. 1).…”
Section: Identification Of Radical Productssupporting
confidence: 81%
“…By analogy with the muoniated radicals formed from furan 31,36 we can confidently assign the stronger signals obtained from thiophene and pyrrole to structures 4 and 6. It is significant that these radicals have smaller muon hfcs than the other two (3 and 5), consistent with the extended unpaired spin distribution in the allylic moieties of 4 and 6.…”
Section: Identification Of Radical Productsmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, our own studies (Percival et al, 2014;Mozafari et al, 2016Mozafari et al, , 2017Mozafari et al, , 2018) employ a beam of spinpolarized positive muons (µ + ) which may be stopped in a sample under any desired condition. When the muons thermalize, some of them pick up an electron to form muonium (Mu = µ + e -), which can be considered a light isotope of hydrogen (mµ ≈ mp/9).…”
Section: Introductionmentioning
confidence: 94%